Management of oral mucositis caused by radiotherapy – A comprehensive review - Manisha Singh; Anjana Bagewadi (SRM Journal of Research in Dental Sciences, 2022)
Oral cancer is the malignant neoplasm involving the oral cavity. The treatment of oral cancer is surgery, radiotherapy, and adjuvant chemotherapy. Oral mucositis is the most common side effect when radiotherapy treatment for oral cancer is indicated. High.grade oral mucositis results in the delay of the radiotherapy treatment and increases the cost of maintenance. The preventive measures for radiation.induced mucositis include maintaining oral hygiene, treatment of xerostomia, diet modifications, and low.level laser therapy. This article provides a guide for the practicing oncologists about the current treatment, advances in treatment, and alternative medicine for improving radiation.induced mucositis.